Repetitive construction processes scheduling using mixed-integer linear programming - Jaśkowski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Many construction projects contain several identical or similar units, such as floors in multistory buildings, houses in housing developments, sections of pipelines or highways. Repetitive processes arise from the subdivision of a generalized construction process into specific activities associated with particular units. In many cases it is possible to perform individual processes (repeated in each units) in alternative ways (modes). Regardless of the construction project procurement system, duration and cost are the key factors determining project’s economic efficiency and fulfillment of the owner’s needs and requirements. Minimizing project duration and cost are the most important criteria for schedule optimization. Processes that repeat from unit to unit are realized by specialized crews. Uninterrupted resource utilization becomes an extremely important issue for scheduling repetitive processes to minimize employment costs. In this paper, the problem of selecting appropriate modes and minimizing the total project cost and with a constraint on project duration is presented with respect to the continuity of the crews’ work. The paper uses the mixed integer linear programming to model this problem and uses a case study to illustrate it.